(untitled) (Research, Society and Development, 2022)
Objective: to map the existing technologies for communication of the nursing team in the shift change in pediatric emergency. Method: This is a research protocol, registered on the Open Science Framework platform no. osf.io/2ptyb, based on the recommendations of the Joanna Briggs Institute, following the Preferred Reporting Items for Systematic and Meta-Analyses -Extension for Scoping Reviews checklist. The search will be carried out in August 2022 with the descriptors Health Science and Medical Subject Headings. Two reviewers will screen the titles and abstracts, read the full texts and extract data from the included material. The data will be extracted through a form and presented in the form of a table and/or images and in a descriptive way. For the interpretation of the results, the MAXQDA software will be used, followed by the analysis of similarity and word cloud and the textual corpus based on thematic analysis. This protocol will assist the development of the scoping review to identify gaps and synthesis of knowledge for the conduct of future primary studies.